Pengembangan Sistem Informasi Perpustakan Sekolah Berbasis Website SMPN 13 Satu Atap Desa Punggur Kapuas - Muhamad Thahizzur Akmal Ersa; Yulius Yulius; Fransiskus Selaban Putra; Maria Dominika Heni; Nada Awva (Departement of Mathematics Education, 2023)
The purpose of this research is to develop a website-based library information system. The research method used in this research is Research and Development (R&D). The results of this study prove that the assessment was carried out by 2 system experts with the first assessment of 81.00% and the second assessment of 80.00% indicating that this system is very feasible to use. For content expert assessment, 1 expert with a rating of 78.00% indicates that the content in this information system is feasible to use. The steps in this study use the ADDIE model, the development process is Analysis, Design, Development, Implementation, and Evaluation.